2007
DOI: 10.1007/s00247-006-0401-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of radiographer reporting of paediatric brain CT

Abstract: Selected radiographers could play an effective screening role, but lacking the sensitivity required for detecting significant abnormality, they could not be the final diagnostician. We recommend that the study be repeated after both radiographers have received formal training in interpretation of paediatric brain CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Such discrepancies may have serious clinical implications given that these reports, unlike those of radiology trainees and emergency doctors, are not subsequently checked by a neuroradiologist. Finally, despite the recent interest in cranial CT reporting by neuroradiographers [3], few studies have assessed report discrepancy rates in this group: 1 study assessed 2 radiographers' reports for paediatric head CT and found the accuracy in detecting significant abnormalities to be between 49% and 75% [14]; the only other study has assessed a single radiographer and shown a report sensitivity of 85.4%, which compared favourably with the sensitivity for senior trainees: 87.5% [15]. All these studies have recruited only small numbers of candidates: the maximum number of participants in previous studies assessing head CT reporting has been 18 [8].…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancies may have serious clinical implications given that these reports, unlike those of radiology trainees and emergency doctors, are not subsequently checked by a neuroradiologist. Finally, despite the recent interest in cranial CT reporting by neuroradiographers [3], few studies have assessed report discrepancy rates in this group: 1 study assessed 2 radiographers' reports for paediatric head CT and found the accuracy in detecting significant abnormalities to be between 49% and 75% [14]; the only other study has assessed a single radiographer and shown a report sensitivity of 85.4%, which compared favourably with the sensitivity for senior trainees: 87.5% [15]. All these studies have recruited only small numbers of candidates: the maximum number of participants in previous studies assessing head CT reporting has been 18 [8].…”
Section: Discussionmentioning
confidence: 99%
“…11). Dedicated CT radiographers without training in CT image interpretation have been tested for their ability to detect CT abnormalities by years-of-experience, and they demonstrated a high accuracy with increasing experience [52].…”
Section: Image Interpretationmentioning
confidence: 99%
“…Our training program may also not have been optimal for this specific group of observers. It was developed based on earlier experience by several groups who were successful in training non-radiologists to read imaging studies [5, 11, 21]. We combined both knowledge transfer and hands-on experience in a structured program with direct feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that radiographers can accurately read mammograms [7], plain x-rays [8], intravenous pyelograms [9] and double-contrast barium enemas [10]. Much lower accuracy results have been seen in a study in which non-radiologists evaluated paediatric brain CT but no dedicated training was given in that study [11]. …”
Section: Introductionmentioning
confidence: 99%